Effects of Gluconacetobacter diazotrophicus on seed cane produced through micro-propagated plantlets in sugarcane (Saccharum spp hybrid complex) under sub-tropics - SINGH, R K; SUMAN, ARCHNA; SINGH, J; SINGH, A K; KUMAR, SANJEEV; SINGH, P K; SINGH, R K (The Indian Journal of Agricultural Sciences, 2012)
Field experiment was conducted to evaluate the performance of micropropagated plantlets inoculated in vitro with Gluconacetobacter diazotrophicus on the population counts of diazotroph, plant growth, yield, quality and ultimately planting material of sugarcane cultivar CoS 96268. Maximum cell counts (5.8 × 105 cells/g fresh weight) was obtained in the in vitro, treated micropropagated plantlets-followed by untreated micropropagated plantlets (4.7 × 104 cells/g fresh weight) while it was only 3.7 x104 cells/g fresh weight in conventionally grown plants. The highest cell counts of Gluconacetobacter diazotrophicus was recorded at grand growth stage which decreased at maturity. Inoculation with diazotroph improved dry matter accumulation specially in roots accompanied by higher uptake of nitrogen and potassium in micropropagated plantlets. There was significant increase in number of millable canes, cane length, number of nodes, cane diameter and cane yield. Besides, treated plantlets produced 5.45 and 1.52 times higher planting material (3 budded setts) over conventionally grown plants and un-treated micropropagated plantlets, respectively. Results signify the use of inoculation with diazotrophic bacteria in micropropagated plantlets for faster multiplication of disease-free healthy seed cane of sugarcane varieties for their adoption.